Variation of the Lateral Sacral Artery in relation to Sciatic Neuropathy. (13th November 2014) - Al Talalwah, Waseem; Ali Al Dorazi, Shorok; Soames, Roger
Abstract : The lateral sacral artery usually originates from the posterior trunk of the internal iliac artery. The current study of 342 specimens from 171 cadavers (79 male, 92 female) investigated the origin and course of the lateral sacral artery. It was observed to arise from the posterior trunk in 79.1%. Occasionally it originated from the anterior trunk that occurred in 1%. It arose from the sciatic artery in 8.8%, from the superior gluteal artery in 16.8%, and from the inferior gluteal artery in 5.4%. Conversely, the lateral sacral artery is congenital absence in 0.3%. In addition, the lateral sacral artery was single, double, triple, and quadruple in 77.2%, 19.8%, 2.3%, and 0.3%, respectively. Consequently, variability of the lateral sacral artery origin is due to vascular demand as the lateral sacral artery plexus does arise from the earlier trunk development. With variability of the lateral sacral artery origin, there is a variability of the sciatic nerve supply. Knowing the variability of origins, surgeons have to avoid prolonged ligation of the internal iliac artery or its posterior trunk during surgical procedures which may lead to sciatic neuropathy. Therefore, the lateral sacral artery origin, course, and branches are important for clinicians to improve their knowledge and patient management.